2019
DOI: 10.3390/ijms20071556
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Rhes Increases MDMA-Induced Neuroinflammation and Dopamine Neuron Degeneration: Role of Gender and Age

Abstract: Ras homolog enriched in striatum (Rhes) is a protein that exerts important physiological functions and modulates psychostimulant drug effects. On this basis, the object of this study was to assess 3,4-methylenedioxymethamphetamine (MDMA) effects on microglial (CD11b) and astroglial (GFAP) activation and on dopamine neuron degeneration (TH) in wild-type (WT) and Rhes knockout (KO) male and female mice of different ages. Motor activity was also evaluated. Adult (3 months) MDMA-treated mice displayed an increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 62 publications
3
18
0
Order By: Relevance
“…In agreement with this evidence, recent studies reported that lack of Rhes in mice enhanced the motor stimulation associated to amphetamine 17 , phencyclidine 17 , MDMA 25 administration, suggesting a primary role of this protein in modulating psychostimulants responses.…”
Section: Introductionsupporting
confidence: 73%
“…In agreement with this evidence, recent studies reported that lack of Rhes in mice enhanced the motor stimulation associated to amphetamine 17 , phencyclidine 17 , MDMA 25 administration, suggesting a primary role of this protein in modulating psychostimulants responses.…”
Section: Introductionsupporting
confidence: 73%
“…Accordingly, reserpine-treated female rats did not show any reduction of tyrosine hydroxylase immunoreactivity in the SNc and dorsal striatum compared to males [90]. The lack of Ras homolog enriched in striatum (Rhes), a protein that exert pleiotropic effects on cell function, in KO mice induced a decrease in tyrosine hydroxylase expression in males only, while KO females showed resistance to DA neuron degeneration, which tended to decrease only with aging [91,92]. Interestingly, neuronal loss in male SNc is accompanied by a significant reduction in total ganglioside content, especially neuronal-or synaptic-enriched gangliosides GD1a and GT1b.…”
Section: Dopaminergic Neurodegenerationmentioning
confidence: 93%
“…Cells were sampled with a 40× objective through a defined depth with a guard zone of 2 µm. Coefficients of error ranged from 0.05 to 0.1 (Costa et al, 2017(Costa et al, , 2019a.…”
Section: Stereological Counting Of Th-immunoreactive Neurons In the Sncmentioning
confidence: 99%